The strategy in learning - Huerta Rosales, Moisés (2016)
The learning strategy shows how people who learn, think and solve problems successfully are strategic. So a person is strategic plans, evaluates and regulates their own mental processes.Therefore, the use of strategies in learning aims to select, combine and redesign cognitive processes. A learning strategy is a sequence of activities; consequently, an apprentice strategist must learn to design, plan the purposes of learning, and organize and lead those processes to achieve the desired competition. Strategic training therefore lies in both the acquisition of planning processes, the forecasting of instruments and the implementation and implementation of strategies to achieve the desired performance.